2004
DOI: 10.1074/jbc.m403858200
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Divalent Metal Ions in the Active Site of Poly(A)-specific Ribonuclease

Abstract: Poly(A)-specific ribonuclease (PARN) is a highly poly(A)-specific 3-exoribonuclease that efficiently degrades mRNA poly(A) tails. PARN belongs to the DEDD family of nucleases, and four conserved residues are essential for PARN activity, i.e. Asp-28, Glu-30, Asp-292, and Asp-382. Here we have investigated how catalytically important divalent metal ions are coordinated in the active site of PARN. Each of the conserved amino acid residues was substituted with cysteines, and it was found that all four mutants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
5
36
0
2
Order By: Relevance
“…Fig. 7B also shows that the final product obtained in the presence of Mn 2ϩ ions was slightly smaller than that seen in the presence of Mg 2ϩ or Zn 2ϩ , suggesting that binding to different metal ions might affect the activity of the SARS-CoV ExoN by inducing subtle structural differences in the active site, as reported for several other nucleases (21,23). The data presented in Figs.…”
Section: Metal Ion Requirements Of Sars-cov Exonsupporting
confidence: 59%
“…Fig. 7B also shows that the final product obtained in the presence of Mn 2ϩ ions was slightly smaller than that seen in the presence of Mg 2ϩ or Zn 2ϩ , suggesting that binding to different metal ions might affect the activity of the SARS-CoV ExoN by inducing subtle structural differences in the active site, as reported for several other nucleases (21,23). The data presented in Figs.…”
Section: Metal Ion Requirements Of Sars-cov Exonsupporting
confidence: 59%
“…The interaction with the cap structure enhances efficiency of deadenylation [22][23][24] and amplifies the processivity of the enzymatic action [25]. PARN belongs to the RNase D family of nucleases [26] which is a part of the superfamily of DEDD nucleases [27] that are characterized by the presence of four conserved acidic amino acids (Asp, Glu, Asp, Asp) in the catalytic centre and require divalent metal ions for efficient catalysis [28,29]. Our recent work revealed that the active site of PARN per se harbors specificity for recognition of adenosine residues and that the nucleotide context around the scissile bond determines the efficiency of the hydrolysis [30].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…PARN also contains a RNA recognition motif (RRM), missing from the crystal structure, which harbours both poly(A) and cap binding properties [18] and stabilizes the overall structure of the enzyme [19]. The catalytic active site contains four invariant acidic amino acid residues, one glutamic acid and three aspartic acids (Asp28, Glu30, Asp292, and Asp382 in PARN) that coordinate catalytically essential divalent metal ions, such as Mg 2 þ [20,21], while His377 has been proposed to be essential for catalytic activity [17]. However, the crystal structure of the truncated PARN showed that no Mg(II) ions are harbored in the active site of the enzyme [17].…”
Section: Introductionmentioning
confidence: 99%